Diastereoselective synthesis of beta-ether derivatives of artemisinin, an antimalarial drug: the effect of nitrile on stereoselectivity - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2016)
Malaria is a life-threatening disease affecting a major portion of the world's population with considerable loss of human life. Artemisinin, isolated from Artemisia annua, its oil- and water-soluble derivatives, and other known antimalarials are recommended for artemisinin combination therapy by the World Health Organization. We have established a method for the stereoselective synthesis of beta-ether derivatives of dihydroartemisinin in high yield and high diastereoselectivity. The reaction either in acetonitrile or dichloromethane/trichloroacetonitrile (6:1) mixtures at 0 degrees C or room temperature, respectively, furnished the antimalarial drugs artemether 3 or arteether 4 in high yield with a high diastereomeric ratio. The effect the nitrile has on the yield and stereoselectivity is mechanistically explained.
Keywords: antimalarials; arteethers; artemisinin; nitriles; trichloroacetimidates

Histidinal-based potent antimalarial agents - Meena, Chhuttan L.; Hingamire, Tejashri; Gupta, Tanya; Deshmukh, Bhagyashree; Karmodiya, Krishanpal; Joshi, Rakesh; Shanmugam, Dhanasekaran; Sanjayan, Gangadhar J. (ChemMedChem, 2023)
Herein we report the synthesis and evaluation of peptide-histidinal conjugated drug scaffolds, which have the potential to target the hemoglobin-degrading proteases falcipain-2/3 from the human malaria parasite. Scaffolds with various substitutions were tested for antimalarial activity, and compounds 8 g, 8 h, and 15 exhibited EC50 values of similar to 0.018 mu M, similar to 0.069 mu M, and similar to 0.02 mu M, respectively. Structure-based docking studies on falcipain-2/3 proteases (PDB:2GHU and PDB:3BWK) revealed that compounds 8 g, 8 h, and 15 interact strongly with binding sites of falcipain-2/3 in a substrate-like manner. In silico ADME studies revealed that the molecules of interest showed no or minimal violations of drug-likeness parameters. Further, phenotypic assays revealed that compound 8 g and its biotinylated version inhibit hemoglobin degradation in the parasite food vacuole. The identification of falcipain-2/3 targeting potent inhibitors of the malaria parasite can serve as a starting point for the development of lead compounds as future antimalarial drug candidates.
Keywords: artemisinin; chloroquine; digestive vacuole; docking; falcipains; falciparum; P

Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation

Late-stage C(sp(2))-H arylation of artemisinic acid and arteannuin B: effect of olefin migration towards synthesis of C-13 arylated artemisinin derivatives - Paul, Sayantan; Ghodake, Balaji M. M.; Bhattacharya, Asish K. K. (Chemistry-An Asian Journal, 2023)
In recent years, C-H bond functionalization has emerged as a pivotal tool for late-stage functionalization of complex natural products for the synthesis of potent biologically active derivatives. Artemisinin and its C-12 functionalized semi-synthetic derivatives are well-known clinically used anti-malarial drugs due to the presence of the essential 1,2,4-trioxane pharmacophore. However, in the wake of parasite developing resistance against artemisinin-based drugs, we conceptualized the synthesis of C-13 functionalized artemisinin derivatives as new antimalarials. In this regard, we envisaged that artemisinic acid could be a suitable precursor for the synthesis of C-13 functionalized artemisinin derivatives. Herein, we report C-13 arylation of artemisinic acid, a sesquiterpene acid and our attempts towards synthesis of C-13 arylated artemisinin derivatives. However, all our efforts resulted in the formation of a novel ring-contracted rearranged product. Additionally, we have extended our developed protocol for C-13 arylation of arteannuin B, a sesquiterpene lactone epoxide considered to be the biogenetic precursor of artemisinic acid. Indeed, the synthesis of C-13 arylated arteannuin B renders our developed protocol to be effective in sesquiterpene lactone as well.
Keywords: Arteannuin B; Artemisinic acid; artemisinin; C-H functionalization; Pd-catalysis